Acculturation of Russian immigrants in Finland : cultural maintenance, interpersonal communications and language skills - Aghaee, Atefeh (2014)
Cultural maintenance is an important dimension of acculturation, and immigrants' attitude towards this phenomenon has been shown to vary by the change of other factors, like the intergroup relations. The present quantitative study was an attempt to study the acculturation of Russian immigrants in Finland, investigating their perceived cultural maintenance, cultural maintenance attitudes, interpersonal communication as well as language skills of immigrants.\vspace*{.50cm}